2015
DOI: 10.1515/auom-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Hop Domination in Graphs-II

Abstract: Let G = (V, E) be a graph. A set S ⊂ V (G) is a hop dominating set of G if for every v ∈ V − S, there exists u ∈ S such that d(u, v) = 2. The minimum cardinality of a hop dominating set of G is called a hop domination number of G and is denoted by γ h (G). In this paper we characterize the family of trees and unicyclic graphs for which γ h (G) = γt(G) and γ h (G) = γc(G) where γt(G) and γc(G) are the total domination and connected domination numbers of G respectively. We then present the strong equality of hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 5 publications
0
52
0
Order By: Relevance
“…Recently, Natarajan and Ayyaswamy [6] introduced and studied the concept of hop domination in a graph. In another study, Ayyaswamy et al [2] investigated the same concept and gave bounds of the hop domination number of some graphs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Natarajan and Ayyaswamy [6] introduced and studied the concept of hop domination in a graph. In another study, Ayyaswamy et al [2] investigated the same concept and gave bounds of the hop domination number of some graphs.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Ayyaswamy et al [2] investigated the same concept and gave bounds of the hop domination number of some graphs. Henning and Rad [5] also studied the concept and answered a question posed by Ayyaswamy and Natarajan in [6]. They presented probabilistic upper bounds for the hop domination number and showed that the decision problems for the 2-step dominating set and hop dominating set problems are NP-complete for planar bipartite graphs and planar chordal graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ayyaswamy and Natarajan ( [2,9]) initiated a study on a new domination parameter called hop domination number of a graph and characterized the family of trees and unicyclic graphs with equal hop domination number and total domination number. Ayyaswamy et al ( [1]) found some bounds on hop domination number of a tree.…”
Section: Introductionmentioning
confidence: 99%
“…A subset S of vertices of a graph G is a hop dominating set (HDS) if every vertex outside S is at distance two from a vertex of S. The hop domination number, γ h (G), of G is the minimum cardinality of an HDS of G. An HDS of G of minimum cardinality is referred to a γ h (G)-set. The concept of hop domination was further studied, for example, in [1,4,7,9]. For a subset S ⊆ V (G) and a vertex v ∈ V (G), we say that v is hop dominated by S (or S hop dominates v) if either v ∈ S or v ∈ S and d(u, v) = 2 for some vertex u ∈ S. Ayyaswamy and Natarajan [9] also introduced the concept of hop independent domination in graphs.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of hop domination was further studied, for example, in [1,4,7,9]. For a subset S ⊆ V (G) and a vertex v ∈ V (G), we say that v is hop dominated by S (or S hop dominates v) if either v ∈ S or v ∈ S and d(u, v) = 2 for some vertex u ∈ S. Ayyaswamy and Natarajan [9] also introduced the concept of hop independent domination in graphs. A subset S of vertices of a graph G is a hop independent dominating set (HIDS) if S is a HDS and for any pair v, w ∈ S, d(v, w) = 2.…”
Section: Introductionmentioning
confidence: 99%